Practice applications of research. Longitudinal comparison of preterm pain responses to repeated heelsticks. - Evans JC; McCartney EM; Lawhon G; Galloway J (Pediatric Nursing)
Background: Preterm infants receive repeated heelsticks over their hospitalization, yet contradictions exist regarding the influence of prior heelsticks, prior painful procedures, and severity of illness on assessment of the pain responses.Purposes: Compare pain responses to repeated heelsticks in infants of varying gestational age groups, and determine the influence of number of prior heelsticks, total number of prior painful procedures, and severity of illness on pain responses over time.Design and Methods: The descriptive longitudinal design utilized a convenience sample of 81 preterm infants from a Midwestern Level III newborn intensive care unit (NICI).Results: Significant differences in Preterm Infant Pain Profile (PIPP) scores were found between age groups. Both the severity of illness and the total number of prior painful procedures had a significant influence on pain scores.Conclusions: Nurses' use of developmental care and the QuickHeel (TM)device may result in lower pain scores. Higher severity of illness and number of prior heelsticks may lower pain scores.